With the two ¿born the penalty? the origin of subjecting in alterity from Emmanuel Levinas’ work - Fonti, Diego (2016)
This paper begins with the “ending” – both in regards to its termination as well as of its full completion – of the modern subject, which was believed able to structure, legalize and manipulate the whole of reality by the very power of its consciousness. In this regards it will be analyzed how consciousness, intentionally structured, operates in Husser’s work, and the Heidegger’s judgment of this understanding, as well as his own phenomenology of existence. Starting with this presentation, it will be researched how Levinas follows and goes beyond Heidegger, by affirming that he is unable to account for the “origin” of human subjectivity: the nomination and invocation of the Other. The main moment of this article analyses the birth of subjectivity in the answer to this invocation.